Insights into the Sources, Structure, and Action Mechanisms of Quinones on Diabetes: A Review - Tingting Zhang; Mingyue Li; Jingyang Lu; Jia Wang; Min Zhang; Pharkphoom Panichayupakaranant; Haixia Chen (Molecules)
Quinones, one of the oldest organic compounds, are of increasing interest due to their abundant presence in a wide range of natural sources and their remarkable biological activity. These compounds occur naturally in green leafy vegetables, fruits, herbs, animal and marine sources, and fermented products, and have demonstrated promising potential for use in health interventions, particularly in the prevention and management of type 2 diabetes (T2DM). This review aims to investigate the potential of quinones as a health intervention for T2DM from the multidimensional perspective of their sources, types, structure–activity relationship, glucose-lowering mechanism, toxicity reduction, and bioavailability enhancement. Emerging research highlights the hypoglycemic activities of quinones, mainly driven by their redox properties, which lead to covalent binding, and their structural substituent specificity, which leads to their non-covalent binding to biocomplexes. Quinones can improve insulin resistance and regulate glucose homeostasis by modulating mitochondrial function, inflammation, lipid profile, gastrointestinal absorption, and by acting as insulin mimetics. Meanwhile, increasing attention is being given to research focused on mitigating the toxicity of quinones during administration and enhancing their bioavailability. This review offers a critical foundation for the development of quinone-based health therapies and functional foods aimed at diabetes management.